Answer:
y = 1
Explanation:
Using the elimination method, let's use y since the process requires less multiplying, you must have the y's match but one must be negative, to do this, you need to multiply the whole equation by the number needed to match negatively:
3x - 5y = 4
5x + y = 16
Multiply the equation (5x + y = 16) by 5:
5(5x + y = 16)
25x + 5y = 80
Eliminate:
3x - 5y = 4
25x + 5y = 80
___________
28x = 84
Divide both sides by 28:
x = 3
Plug in 3 fro x into one of the equations:
5x + y = 16
5(3) + y = 16
15 + y = 16
y = 1